Servant Leadership, Self Efficacy and Job Satisfaction, on the Performance of Managers of Alahan Panjang Tourism Object, Solok Regency - yulihardi, yulihardi; Yenni Del Rosa; Darman (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This paper to reveal the influence of Servant Leadership, Self efficacy, and Job Satisfaction together on the Performance of Tourism Object Management Groups in the Technical Implementation Unit of the Alahan Panjang Service Office (UPTD), Solok Regency. Partial Influence of Servant Leadership, Self efficacy, and Job Satisfaction on the Performance of Tourism Object Management Groups at UPTD Alahan Panjang, Solok Regency. Methodology/approach –The research method used is quantitative research. The sampling technique used,all Tourism Object Management Groups working within the UPTD Alahan Panjang, Solok Regency, with a total of 50 people. Findings – It was found that. Finding Based on the partial test (test) it was found that there was a significant influence between Servant leadership, Self Efficacy and Work satisfactionon the performance of tourist attraction managers.It was also found that contributed 73.5% with Job Satisfaction as the most dominant variable, while 26.5% was determined by other variables not included in this research. Conclusion:Partially and simultaneously from Servant Leadership, Self efficacy and Job Satisfaction proved to have a positive and significant influence on the Performance of Tourism Object Management Groups at UPTD Alahan Panjang, Solok Regency. Novelty/value – Servant Leadership overcomes the leadership crisis of trust & example in managers in the tourism sector and based on their beliefs about their chances of successfully achieving the tasks carried out with job satisfaction is very important to understand to improve the performance of tourism managers in Solok Regency